Unnatural death [compact disc, unabridged] - Cornwell, Patricia Daniels (Cornwell, Patricia Daniels. Scarpetta series., 2023)
"In this thrilling new installment of Patricia Cornwell's #1 bestselling Scarpetta series, chief medical examiner Dr. Kay Scarpetta finds herself in a Northern Virginia wilderness examining the remains of two campers wanted by federal law enforcement. The victims have been savaged beyond recognition, and other evidence is terrifying and baffling, including a larger-than-life footprint. After one of the most frightening body retrievals of her career, Scarpetta must discover who would commit murders this savage, and why" --